2020
DOI: 10.1038/s41598-020-71489-7
|View full text |Cite
|
Sign up to set email alerts
|

The short isoform of extended synaptotagmin-2 controls Ca2+ dynamics in T cells via interaction with STIM1

Abstract: ca 2+ release-activated Ca 2+ (CRAC) channels elevate cytoplasmic Ca 2+ concentration, which is essential for T cell activation, differentiation and effector functions. T cell receptor stimulation induces depletion of the endoplasmic reticulum (ER) Ca 2+ stores, which is sensed by stromal interaction molecule 1 (STIM1). STIM1 translocates to the ER-plasma membrane (PM) junctions to interact with ORAI1, the pore subunit of the CRAC channels. Here, we show that two members of the extended synaptotagmin (E-Syt) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…Here, we show that the only apparent ultrastructural change occurring during SOCE in non-treated HEK-293 T cells is a cER elongation that is likely mediated by endogenous STIM proteins, indicating that the cER gap distance is not dynamically regulated by the activity of endogenous E-Syt1. An earlier report showed that depletion of both E-Syt1 and E-Syt2 inhibits SOCE in Jurkat T cells but not in HeLa cells ( Woo et al, 2020 ) and our siRNAs targeting either isoform did not inhibit SOCE in HEK-293 T cells (data not shown). This might reflect the expression of distinct isoforms in immune and non-immune cells, with the activating isoform E-Syt2b possibly accounting for the inhibitory effects of E-Syt1 and E-Syt2 silencing in Jurkat T cells.…”
Section: Discussionsupporting
confidence: 44%
“…Here, we show that the only apparent ultrastructural change occurring during SOCE in non-treated HEK-293 T cells is a cER elongation that is likely mediated by endogenous STIM proteins, indicating that the cER gap distance is not dynamically regulated by the activity of endogenous E-Syt1. An earlier report showed that depletion of both E-Syt1 and E-Syt2 inhibits SOCE in Jurkat T cells but not in HeLa cells ( Woo et al, 2020 ) and our siRNAs targeting either isoform did not inhibit SOCE in HEK-293 T cells (data not shown). This might reflect the expression of distinct isoforms in immune and non-immune cells, with the activating isoform E-Syt2b possibly accounting for the inhibitory effects of E-Syt1 and E-Syt2 silencing in Jurkat T cells.…”
Section: Discussionsupporting
confidence: 44%
“…Although fragments of the STIM1/Orai1 interplay with accessory proteins are often wellknown, the complete molecular picture of all interactions is still lacking. Furthermore, it remains unclear whether all these proteins interplay with each other in the same cell at the ER-PM junction or whether this diversity of available ER-PM proteins act in a cell type-specific manner, as it was identified for E-Syts [136,143]. Some proteins may also form ER-PM junctions independently of STIM proteins, opening up the intriguing possibility that different types of junctions form in a cell in response to stimulation by varying amounts of agonist.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, while deletion of the STIM1 PIP 2 binding site, specifically the lysine-rich region, at the very end of the STIM1 C-terminus (STIM1 ∆K) was unable to translocate into puncta in the absence of Orai1, only co-expression with E-Syt2S triggered STIM1 ∆K oligomerization. The long isoform of the E-Syt2 protein, E-Syt2L, is assumed to act inhibitory on STIM1 recruitment to the PM [143] (Table 1).…”
Section: Extended Synaptotagminsmentioning
confidence: 99%
“…STIM proteins are anchored to the ER membrane and function as Ca 2+ sensors that detect ER Ca 2+ depletion. After sensing ER Ca 2+ depletion, STIM1 and STIM2 translocate to the ER-plasma membrane (PM) junctions defined by junctional proteins (Woo et al 2020). Interaction between STIM1 and Orai1 at the ER-PM junction results in the activation and opening of the CRAC channels, thereupon producing a sustained increase in intracellular calcium levels (Fig.…”
Section: Calcium Signaling As a Pathological Mechanism Of Th17 Cell Differentiationmentioning
confidence: 99%